Degron-independent recruitment of KAT2A expands the target space of CRBN molecular glues - Samuel Ojeda; Meng Wang; Kheewoong Baek; Wallace Bourgeois; Alba Sommerschield; Hong Yue; Rebecca J. Metivier; Panos Karagiannis; Talya S. Levitz; Yuan Xiong; Katherine A. Donovan; Scott A. Armstrong; et al. (Science, 2026)
Lysine acetyltransferases (KATs) cooperate with oncogenes such as c-Myc, estrogen receptor, and lysine methyltransferase 2A (KMT2A) fusions to sustain malignant programs. Targeting of KAT proteins has shown clinical efficacy; however, achieving homolog selectivity for most KATs remains a major challenge. By extending cereblon (CRBN)–based molecular glues beyond the canonical degron space, we developed an exquisitely selective degrader of KAT2A. Cryo–electron microscopy revealed that CRBN recruits KAT2A independently of a degron; instead, the molecular glue engages a surface-exposed tyrosine, mimicking antibody-like molecular recognition. Selective KAT2A degradation leads to potent ablation of histone H3 lysine 9 acetylation (H3K9Ac), antiproliferative effects in acute myeloid leukemia cell lines, and in vivo efficacy in a patient-derived xenograft model, establishing KAT2A as a targetable vulnerability to treat a wide range of malignancies. More generally, degron-independent recruitment extends the CRBN-targetable proteome.